THE INFLUENCE OF WORK ENVIRONMENT AND FACILITIES ON EMPLOYEE PERFORMANCE IN THE PLN UP2B MAKASSAR SYSTEM - Firdaus Firdaus; A. Syarifah Aulia; Nurul Asia; Nur Inayah Idil (Jurusan Pendidikan Teknik Elektro, 2024)
In the middle development increasing business​ developing , performance employee become element it's important who gets it attention main from company Study This aim For know influence environment work and facilities Work to performance employee at PT PLN UP2B Makassar System . Study quantitative This use design multiple linear regression with population as many as 35 employees were taken as sample through total sampling technique . Data is collected through observations and questionnaires , then analyzed using the T test and F test. The results show that environment work (X1) has influence positive and significant to performance employees (b = 0.592, p < 0.05), whereas facility (X2) has influence positive However No significant (b = 0.220, p > 0.05). The F test shows that environment work and facilities in a way simultaneous influential significant to performance employees (p = 0.001). The R square value of 0.586 shows that 58.6% variation performance employee can explained by the second variable this , while 41.4% is influenced by other variables that are not researched . Study This conclude that combination environment work and facilities contribute significant to performance employee at PT PLN UP2B Makassar System .